Health status correlates of malnutrition diagnosed based on the GLIM criteria in older Polish adults—Results of the PolSenior 2 study - Aleksandra Kaluźniak-Szymanowska; Ewa Deskur-Śmielecka; Roma Krzymińska-Siemaszko; Arkadiusz Styszyński; Sławomir Tobis; Marta Lewandowicz; Jerzy Chudek; Tomasz Kostka; Małgorzata Mossakowska; Karolina Piotrowicz; Hanna Kujawska-Danecka; Katarzyna Wieczorowska-Tobis (PLoS ONE, 2025)
Introduction Older individuals are at risk of malnutrition resulting from chronic diseases-related body and muscle mass reduction. In turn, nutritional deficiencies may enhance catabolic processes, leading to accelerated aging and comorbidity, thus creating a vicious cycle. Our study aimed to assess the prevalence of malnutrition using the Global Leadership Initiative on Malnutrition (GLIM) criteria and to determine the health correlates of malnutrition in a representative sample of community-dwelling older adults. Methods We used the GLIM criteria to diagnose malnutrition in 5,614 participants of the PolSenior2 study. The PolSenior2 study was a population-based survey designed to assess the medical, psychological, social, and economic characteristics of community-dwelling older adults. Results Malnutrition was diagnosed in 13.4% of the participants using the GLIM criteria. Results of multiple logistic regression showed that the risk of depression [OR 4.18, p<0.001], peptic ulcer disease [OR 2.73, p<0.001], past stroke [OR 1.71, p<0.001], cognitive impairment [OR 1.34, p = 0.015], and chronic pain [OR 1.23, p = 0.046] were independent correlates of malnutrition. Conclusion Due to the high risk of malnutrition, special attention should be paid to individuals in late old age. Suspected malnutrition should also be considered in people at risk of depression, with peptic ulcer disease, past stroke, and cognitive impairment. Chronic pain should also prompt the diagnosis for malnutrition.